Gendered Justice: Intimate Partner Violence and the Criminal Justice System - Garcia, Venessa; McManimon, Patrick (Issues in Crime and Justice, 2012)
Gendered Justice takes a unique, multi-layered look at the various elements that factor into our understanding of domestic violence and how the criminal justice system handles situations of domestic violence. The book focuses primarily on the role of gender, but also considers socio-economic status and race. Illustrated with case studies throughout, the book introduces major themes, such as the social construction of gender and victimology, as well as topics such as the portrayal of intimate partner violence in the media and how it sh